PENGARUH DEPENDENCY RATIO, GINI RATIO, DAN TINGKAT PARTISIPASI ANGKATAN KERJA TERHADAP KEMISKINAN DI SUMATERA UTARA TAHUN 2001-2024 - Era Widia Br Sinaga; Muhammad Yusuf (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2026)
Poverty is a multidimensional problem that remains a major challenge for North Sumatra despite relatively strong economic growth. This study aims to analyze the effect of the Dependency Ratio, Gini Ratio, and Labor Force Participation Rate (LFPR) on poverty in North Sumatra Province during the period 2001–2024. Using a quantitative approach with time-series data and the Ordinary Least Squares (OLS) estimation method, the results show that the Dependency Ratio has a positive and significant effect on poverty, meaning that each one percent increase in the dependency ratio raises the number of poor people by 31.74 thousand. The Gini Ratio has a negative and significant effect, explained by the Kuznets Hypothesis and the Selective Poverty Exit mechanism. LFPR has a negative and significant effect, with each one percent increase reducing poverty by 16.39 thousand people. Simultaneously, the three variables explain 82.84 percent of the variation in poverty (Adjusted R² = 0.8284), confirming that poverty in North Sumatra is a multidimensional structural phenomenon. Policy implications emphasize the urgency of optimizing the demographic dividend, ensuring inclusive economic growth, and improving the quality of employment.